Development, Optimization and Validation of LC-MS/MS Method for Multi-Mycotoxin Detection in Cereals - Soleimany, Farhang (2011)
Mycotoxins are fungal natural metabolites that have a wide range of toxic effects. Among hundreds of mycotoxins, aflatoxins (AFs) (AFB1, AFB2, AFG1, and AFG2), ochratoxin A (OTA), zearalenone (ZEA), deoxynivalenol (DON), fumonisins (FB1 and FB2,), T2 and HT2-toxins are the major health concerns for humans and domestic animals. First, an HPLC method has been developed to investigate the separation of mycotoxins in liquid chromatography. Two derivatization systems, photochemical and chemical methods were applied for derivatization of AFB1 and AFG1, as well as FB1 and FB2, respectively. Then, a LC-MS/MS method has been developed by evaluating the effect of LC column (50 and 150 mm), organic modifier (methanol and acetonitrile) ionization process (ESI, APCI) and ionization mode (positive and negative) on separation and determination of mycotoxins. Then the developed method was optimized for simultaneous determination of the 11 mycotoxins. Response surface methodology (RSM) was used to optimize the LC conditions. The effect of organic solvent percentage at the beginning (0-20%) and end (75-95%) of gradient mobile phase, acid concentration in aqueous phase (0-1%), and flow rate (100-300 μl/min) have been investigated for optimization of LC responses peak area and signal to noise ratio (S/N). The optimized responses obtained using following conditions: organic solvent of 5% at start and 95% at the end of gradient mobile phase, 0.1% acid concentration, and 250 μl/min flow rate. In addition, best sample preparation procedure have been selected by evaluating the effects of two different common types of solvent extraction methods (one step and two step extraction) and four types of clean-up methods including Oasis HLB, MycoSep, immunoaffinity column (IAC) and no clean-up on mycotoxins recoveries. The results of the study showed that the best recoveries (79-109%) for all mycotoxins would be obtained by using one step extraction with no clean up. Finally, the optimized LC-MS/MS method was validated by measuring the selectivity, sensitivity, linearity, accuracy and precision. Limit of Detection (LOD) for AFB1, AFB2, AFG1, AFG2, DON, T2-Toxin, HT2-Toxin, FB1, FB2, OTA and ZEA was 0.05, 0.25, 0.05, 0.5, 5, 2, 2, 10, 10, 0.01, and 0.1, whereas the Limit of Quantification (LOQ) was 0.1, 0.5, 0.1, 1, 10, 4, 4, 20, 20, 0.02, and 0.2 ppb, respectively. Finally, the optimized and validated LC-MS/MS method was applied on real cereal samples (rice, barley, oat, wheat and maize) collected from Malaysian markets. The results showed applicability of the aforementioned method for being used as fast routine method with high accuracy and precision for simultaneous determination of mycotoxins in cereal.